2014
DOI: 10.1007/s12024-014-9584-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of laryngeal fractures in decomposed bodies using microfocus computed tomography (mfCT)

Abstract: Postmortem computed tomography (CT) is now routinely performed in forensic autopsies. Microfocus computed tomography (mfCT) has attracted recent attention because it can provide more detailed information than routine postmortem CT can. This feasibility study evaluated the usefulness of mfCT for examination of the hyoid bone and thyroid cartilage in cases of suspected strangulation, where advanced decomposition precludes detection of petechial hemorrhages and hemorrhages adjacent to fractures. The results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In particular, it was clearly demonstrated that in-depth analyses of the characteristic features of cut marks on bone can be capable of linking injuries to specific wounding weapons, thereby providing an important contribution to the reconstruction of the events [5][6][7][8][9][10]. Starting from the results obtained on bone, some studies have also focused on sharp force injuries on soft tissues, blood vessels, organs, and cartilage [17,18,21,22]. Costal cartilage can be very important in real case scenarios as it is injured in many cases of stab wounds to the chest.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was clearly demonstrated that in-depth analyses of the characteristic features of cut marks on bone can be capable of linking injuries to specific wounding weapons, thereby providing an important contribution to the reconstruction of the events [5][6][7][8][9][10]. Starting from the results obtained on bone, some studies have also focused on sharp force injuries on soft tissues, blood vessels, organs, and cartilage [17,18,21,22]. Costal cartilage can be very important in real case scenarios as it is injured in many cases of stab wounds to the chest.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study PMCT was able to provide more information, which may have led to slightly a higher percentage of fractures of the laryngeal structures. 22 Another limitation to the present study was that subjects with progressed decomposition, soft tissue emphysema and thermal injuries, and even those with fierce puncture attempts for a central line in agonal or pre-terminal emergency situations, had to be excluded. Although decompositional changes exhibit another gas pattern as the gas bubble sign, advanced putrefaction can obscure this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high-definition 3D reconstructions of micro-CT images of the larynx allowed the detection of thin fracture lines of the superior horn of the thyroid cartilage and of the hyoid bone (Fig. 3C) in cases of strangulation [11,16], also when advanced decomposition precluded the detection of soft tissues injuries [17]. Moreover, micro-CT has been proved useful to identify morphological features observable in the normal population which might have been misinterpreted as real fractures (i.e., discontinuity on the inferior thyroid margin) [18].…”
Section: Fracturementioning
confidence: 99%